Effects of aquatic exercise program versus on-land exercise program on cancer-related fatigue, neuropathy, activity and participation, quality of life, and return to work for cancer patients: study protocol for a randomized controlled trial - Michal Nissim; Yakir Rottenberg; Naama Karniel; Navah Z. Ratzon (BMC, 2024)
Abstract Background Exercise has shown positive effects on fatigue, exhaustion, neuropathy, and quality of life in cancer patients. While on-land exercises have been studied, the aquatic environment offers unique advantages. Water's density and viscosity provide resistance, enhancing muscle strength, while hydrostatic pressure improves venous return. This trial aims to investigate the effect of aquatic exercises on time to return to work, work hours, work-related difficulties, daily life activity and participation, quality of life, exhaustion, fatigue, and neuropathy among cancer patients, compared to on-land exercise intervention group and a non-exercise group. Methods This randomized controlled trial will include 150 cancer patients aged 18-65 years with stage III colon cancer or breast cancer patients with lymph node involvement. Participants in the aquatic exercise intervention group will undergo an 8-week, twice-weekly group-based Ai-Chi program, while the on-land exercise group will perform identical exercise. The control group will not engage in any exercise. The primary outcome will be assessed using an employment barriers questionnaire, capturing return to work date and working hours and daily life participation and activity and quality of life. Secondary outcomes include exhaustion, fatigue, and neuropathy. Data will be collected at baseline, post-intervention (8 weeks), and at 3,12, and 24 months. Mixed variance analyses will explore relationships among groups and over time for independent variables, with separate analyses for each dependent variable. Discussion The potential benefits include an earlier return to work for patients, reducing their need for social and economic support. The study's implications on socio-economic policies are noteworthy, as a successful intervention could offer a cost-effective and non-invasive solution, improving patients' quality of life and increasing their participation in daily activities. This, in turn, could lead to a faster return to work, contributing to both personal well-being and broader societal interests by reducing reliance on social services. Trial registration The trial is registered at ClinicalTrials.gov NCT05427344 (22 June 2022).